Epigenetic regulation of chondrocyte differentiation - Kenji Hata, DDS, PhD (Elsevier, 2015)
Chondrocytes play an essential role in endochondral bone development, which is requisite for mammalian skeletal development. During endochondral bone development, chondrocytes undergo well-organized stages of sequential differentiation, including proliferation and hypertrophy, a process harmoniously modulated by various transcription factors. Epigenetics, including DNA methylation and histone modification, has recently emerged as an essential regulatory system for gene expression, not only in physiological conditions, but also in human disease. During chondrocyte differentiation, transcriptional co-regulators, which form transcriptional protein complexes with specific transcription factors, are predominantly involved in this epigenetic process and cooperatively regulate chondrocyte gene expression. Importantly, several studies indicate that epigenetic regulators correlate with cartilage-related diseases, such as osteoarthritis, and are noted as a potential therapeutic target. Here, current studies of epigenetic regulation of chondrocyte differentiation are reviewed and novel aspects for the molecular mechanisms involved in chondrogenesis are introduced.